Fabrication of a tailorable polystyrene nanoscale mesh of honeycomb morphology using nano sphere lithography - Sharma A.; Jaiswal A.; Jaiswal R.P. (My University, 2025)
Surface morphology of a substrate is altered to achieve adhesion-, thermal-, electrical-, electrochemical- and optical-enhancements in many applications in the field of interfacial engineering. This study presented an approach based on nanosphere lithography (NSL) to produce a tailorable polystyrene (PS) nanoscale mesh with ‘honeycomb’ morphology. First, silica nanoparticles of uniform-size, ranging from 100 to 1500 nm, were synthesized using Stober method. These silica nanoparticles were made to self-assemble on a silicon wafer to form a 2-D hexagonal-packed array through spin coating. The process parameters were optimized at every fabrication step to ensure the monolayer formation of silica nanospheres on a silicon wafer. The inter-particle space in the monolayer was filled with PS without covering the silica nanospheres using dewetting. The etching of silica nanospheres in the subsequent step resulted in the fabrication of PS honeycomb nano-mesh. Such PS honeycomb mesh can be used as a mask or etch-resist layer for selective surface treatments (physical or chemical) in many applications to create a periodic and controllable surface topography. As the NSL is highly inexpensive and the PS for the purpose of etch mask can be obtained directly from waste materials, the PS honeycomb mesh can be produced at very low-cost. © 2022 Elsevier B.V.